2005
DOI: 10.1111/j.1365-2796.2005.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Toll‐like receptor 4 (TLR‐4) variants on intima‐media thickness and monocyte‐derived macrophage response to LPS

Abstract: Abstract. Norata GD, Garlaschelli K, Ongari M, Raselli S, Grigore L, Benvenuto F, Maggi FM, Catapano AL (University of Milan; and Center for the Study of Atherosclerosis, Ospedale Bassini, Cinisello Balsamo; Italy). Effect of the Toll-like receptor 4 (TLR-4) variants on intima-media thickness and monocyte-derived macrophage response to LPS. J Intern Med 2005; 258: 21-27.Objectives. Toll-like receptor 4 (TLR-4) is believed to contribute to the initiation and progression of atherosclerosis. The association of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 37 publications
(77 reference statements)
3
34
0
1
Order By: Relevance
“…Some literature data agree with the results of our study, while others show contrasting results (Arbour et al, 2000;Child et al, 2003;Erridge et al, 2003;Heesen et al, 2003;Imahara et al, 2005;Michel et al, 2003;Norata et al, 2005;Read et al, 2001;Schippers et al, 2005;Werner et al, 2003;von Aulock et al, 2003;Yang et al, 2004). The different associations between the genotypes of +896A/ G SNP and the levels of inflammatory mediators evidenced in different studies may be ascribed to some factors.…”
Section: Lps Stimulationsupporting
confidence: 90%
See 1 more Smart Citation
“…Some literature data agree with the results of our study, while others show contrasting results (Arbour et al, 2000;Child et al, 2003;Erridge et al, 2003;Heesen et al, 2003;Imahara et al, 2005;Michel et al, 2003;Norata et al, 2005;Read et al, 2001;Schippers et al, 2005;Werner et al, 2003;von Aulock et al, 2003;Yang et al, 2004). The different associations between the genotypes of +896A/ G SNP and the levels of inflammatory mediators evidenced in different studies may be ascribed to some factors.…”
Section: Lps Stimulationsupporting
confidence: 90%
“…One or more functional SNPs in one or more genes might be responsible. Accordingly, recent studies have suggested the role of +896A/G TLR4 SNP in cytokine and eicosanoid production (Arbour et al, 2000;Ferwerda et al, 2007Ferwerda et al, , 2008Hoshino et al, 1999;Michel et al, 2003;Norata et al, 2005;Poltorak et al, 1998;von Aulock et al, 2003;Werner et al, 2003). On the other hand, an association of this TLR4 SNP with an increased risk of Gram negative infections and septic shock has been demonstrated (Agnese et al, 2002;Lorenz et al, 2002;Schrö der and Schumann, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The subjects signed an informed consent, and this study was approved by the Ethics Committee of the Centre and conducted under the principles of the Declaration of Helsinki. The clinical outcome measures, such as triglycerides, high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), total cholesterol, systolic and diastolic blood pressure (SBP and DBP), body-mass index (BMI), waist/hip ratio, and cardiovascular risk calculated according to the Framingham algorithm (RCV), were obtained as previously described (27,28). Glucose was measured using the Trinder enzymatic assay and the Cobas Mira Plus analyser (Horiba, Montpellier, ABX, France), while ApoAI and ApoB were measured following turbidimetric analysis and processing in the Cobas Mira Plus analyser.…”
Section: Methodsmentioning
confidence: 99%
“…Data on insulin plasma levels and homeostasis model assessment (HOMA) are available from 300 randomly selected subjects. IMT was evaluated in all subjects at the beginning of the study (IMT 0 ) and after 2 years of follow-up (27) and data are presented as IMT progression (DIMT). To avoid any confounding effect due to pharmacological treatment, among the subjects enrolled in the PLIC study, we excluded 291 subjects taking medication for dyslipidemia and/or diabetes and we randomly selected 1090 subjects stratified according to cardiovascular risk for the analysis of resistin plasma levels.…”
Section: Methodsmentioning
confidence: 99%
“…Five standardized points 5, 10, 20, 25, and 30 mm from the carotid bulb were measured in both arteries and averaged to calculate the mean IMT for each subject. 8 Circulating concentrations of total leptin were measured using a commercial radioimmunoassay kit for human leptin (Linco Research Inc, St. Louis, Mo) and plasma adiponectin levels (all the isoforms) were measured using a commercial enzyme-linked immunosorbent assay kit (Assaypro, Wienfield, Mo). The presence of metabolic syndrome was defined according to the National Cholesterol Program, Adult Treatment Panel III (NCP-ATPIII) guidelines.…”
Section: Methodsmentioning
confidence: 99%